THE ROLE OF GUIDANCE AND COUNSELING IN ASSISTING ODHIV (PEOPLE WITH HIV) FOR DISCLOSURE TO FAMILY AND CLOSE PEOPLE - Muhammad Iqbal Aliyudin (Universitas Pendidikan Indonesia, 2023)
As a counseling teacher or counselor who believes that counseling services are for all, of course as we also want to help ODHIV, or we also want to help prevent HIV transmission but just wanting is not enough we need to have the provisions or knowledge, so here the author uses the method literature review, offers a little provision that hopes to be useful for counseling teachers or counselors who have a desire to help ODHIV to disclose to family, friends and relatives.